Pengaruh Kualitas Layanan dan Produk terhadap Kepuasan Pelanggan Kopi Sejuta Jiwa (Studi Kasus pada Mahasiswa FEB Universitas Negeri Jakarta) - Effendi, Ahmad Haidar; Azahra, Nabila Nur; Rahimah, Nabilah Khansa; Az'Zahra, Siti Fatimah; Hiwari, Rosyad Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
The mobile fast coffee industry in Indonesia is experiencing rapid growth, making service quality and product quality key factors in shaping customer satisfaction. This study aims to analyze the influence of these two aspects on customers of Kopi Sejuta Jiwa using a descriptive qualitative method. Respondents were selected through purposive sampling and consisted of students from Universitas Negeri Jakarta who had previously purchased Kopi Sejuta Jiwa products. Data were collected through open-ended questionnaires that explored customer experiences related to service friendliness, responsiveness, transaction convenience, taste consistency, menu variety, and raw material quality. The findings indicate that customers perceive both service quality and product quality positively, although suggestions were made regarding adjustments to sweetness levels, expansion of menu variety, and broader sales locations. Overall, the results show that improvements in service and product quality play an important role in strengthening customer satisfaction and loyalty.